IMPLEMENTASI PENDIDIKAN IPS DALAM PEMBELAJARAN IPS DI SEKOLAH - Muhammad Zoher Hilmi (Jurnal Ilmiah Mandala Education (JIME), 2017)
Social science education is a simplification of the social sciences and is an interdisciplinary science, so social science education examines a problem from different perspectives of social science in an integrated way. The purpose of social science education is to make good citizens in the sense of being able to understand the differences and be able to solve problems appropriately because it is supported by information and facts. Besides that, social science education output is expected to have sensitivity to social problems and social participation in society. On the other hand, implementation of social science education in social science learning is faced with various obstacles, so the nature and purpose of social science education can not be achieved fully